Boride formation behaviour and their effect on tensile ductility in cast TiAl-based alloys. (October 2020) - Li, Jing; Jeffs, Spencer; Whittaker, Mark; Martin, Nigel
Abstract: Boron has been used to refine the microstructures in TiAl castings, such as low-pressure turbine (LPT) blades, to improve mechanical properties. However, boride precipitates with undesirable morphologies could reduce ductility and even entirely remove the benefits of grain refinement. Boride size and morphology in variant alloys based on Ti45Al2Mn2Nb1B has found to be closely related to alloying element species and solidification conditions, leading to distinctly different boride formation behaviour. It has been shown that Hf promotes the formation of thin curvy boride flakes whilst Ta promotes the formation of thick straight boride ribbons in the studied cooling rate range. The boride crystal structure changes from TiB with the B27 structure for coarse straight boride to TiB with Bf structure for the curvy boride. Curvy borides have the strongest effect in reducing ductility, regardless of alloy composition. Graphical abstract: Image 1 Highlights: Hf promotes the formation of thin curvy boride flakes whilst Ta promotes the formation of thick straight boride ribbons. Coarse long boride has TiB(B27) crystal structure and curvy flake boride has TiB(Bf ) crystal structure. Curvy borides have the strongest effect in reducing ductility, regardless of alloy composition.